Genome-wide identification and expression analysis of the PEBP gene family in Ziziphus jujuba var. spinosa - Ma, Xiaojun; Yang, Xiaozhou; Wang, Xinhong; Tang, Xiaohan; Li, Xuexiang; Geng, Dali; Ma, Yuqing; Pu, Menglin; Shu, Jing (Frontiers in Plant Science, 2026)
Phosphatidylethanolamine-binding proteins (PEBPs) are known to regulate flowering time and morphogenesis in plants. However, their identification and functions in Ziziphus jujuba var. spinosa remain uncharacterized. In this study, seven ZjPEBP genes were identified and were unevenly distributed across six chromosomes. Phylogenetic analysis classified them into four subfamilies: FT-like, TFL1-like, MFT-like, and SMFT-like. The SMFT-like subfamily likely originated from horizontal gene transfer (HGT) of prokaryotic origin, exhibiting high sequence similarity to bacteria. In contrast, the remaining six members expanded through dispersed duplication events and possess conserved structures. Cis-acting element analysis suggests that ZjPEBP genes may be involved in growth, development, light responsiveness, hormone signaling, and stress adaptation. Reverse transcription quantitative PCR (RT-qPCR) revealed tissue-specific expression patterns among ZjPEBP genes. The key flowering regulators ZjFT and ZjTFL1 exhibited antagonistic expression dynamics during fruit-bearing shoot (FBS) development: ZjFT expression peaked when FBS reached 2–4 mm in length, coinciding with the initial stage of floral bud differentiation, whereas ZjTFL1 maintained low expression levels throughout all developmental stages. After flowering, a clear spatiotemporal expression gradient was observed, with ZjFT expression in basal leaves being significantly higher than in middle and apical leaves. This expression pattern aligned with the basipetal progression of floral organ differentiation. As the basal and middle sections entered the fruit-setting stage, ZjFT expression was markedly downregulated. Under abscisic acid (ABA) treatment, all ZjPEBP genes were significantly induced, suggesting their potential involvement in both flowering regulation and ABA signaling pathways. Notably, ZjSMFT exhibited the most pronounced response, with expression levels upregulated approximately 400-fold at 24 hours post-treatment. This study provides a systematic characterization of the ZjPEBP gene family in sour jujube, laying a solid foundation for further elucidating the molecular mechanisms of flowering regulation and its potential applications in molecular breeding.